Scaling up biofuels? A critical look at expectations, performance and governance☆. (November 2017) - Goetz, Ariane; German, Laura; Weigelt, Jes
Abstract: This editorial is the introduction to a Special Issue of Scaling Up Biofuels? A Critical Look at Expectations, Performance and Governance which assesses biofuels contribution to sustainability governance and upscaling. The issue aims to contribute to a more informed, evidence-based policy debate on the role of bioenergy for sustainable development. It comprises six review papers that share a solutions-oriented and policy-focused approach towards the assessment of sustainability. Bioenergy production and consumption is not evaluated as an isolated industry or additionality. Instead, it is assessed as an inherent component of the broader social-ecological system and history of which it forms a part. Synthesizing available empirical evidence on performance, and contextualizing the evidence in view of expectations and bioenergy governance in and over time, the papers address the role of biofuels for climate mitigation; their ability to deliver on socio-economic policy expectations; the actual performance in view of risk anticipation and mitigation; the role of state policy considering sector development and sustainability; and the ability of certification schemes to deliver on market conversion, and quality. The synthesis paper draws on the empirical findings to develop a set of sustainability conditions ( sine qua nons ) that have to be considered in processes of policy making and upscaling.